Karakteristik histokimia daun Ridan (Nephelium maingayi Hiern – Sapindaceae) dari Provinsi Riau - Sofiyanti, Nery; Fitmawati, Fitmawati; Isda, Mayta Novaliza; Lestari, Asri Ria (Jurnal Biologi Udayana; Vol 26 No 1 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Ridan ( Nephelium maingayi ) is one of Sapindaceae member, that distributed in Riau Province. However, this species is not widely cultivated due to its small and sour fruit. The aim of this study was to examine the histochemical characteristic of Ridan leaf. The secondary metabolite examined in this study were tannin, alkaloid, flavonoid and lipid. Sample used in this study is mature leaf of Ridan. The clean sample was sliced using hand microtome, and tested by using FeCl3 (tannin), NaOH (flavonoid), Wagner (alkaloid) and Sudan III (lipid). Samples were then observed and documented using digital microscope. The result of this study indicated that leaf of Ridan gave positive result on tannin, alkaloid, lipid and flaovonoid. However, lipid was not found in pith of stipe, cortex and  pith of leaf petiole. The result of this study give additional information on histochemical test of Nephelium .